Progresso da mancha marrom e estimativa da herdabilidade da resistência em genótipos duplo-haplóides de trigo - Mühl, Fabiana Raquel (2009)
Bipolaris brown spot of wheat is a disease that can induce high damage or grain quality and yield of wheat. In Brazil this disease can induce yield losses up to 60% on susceptible wheat varieties. The disease can affect yield of wheat in any growth stage of the plant. Cultural practices as crop rotation, fungicide sparying and resistant cultivars are used to control disease, but resistance appears as the least expensive and desairable strategy. The objectives of this work were caracterize a double-haploid population of the crops BR 18 x Frontana, regarding the disease progress and to study the genetics variability of the resistance to brpwn spot on double-haploid lines of the cross BR 18 x Frontana developed at Embrapa Trigo. The parents and the double-haploid lines werw grown in Green-house and wewrw inoculated with na isolate of Bipolaris sorokiniana with known pathogenicity. The genotypes were visualy evaluated acording to a scale to determine the severity and the AUDPC, to calculate variance and the herdability. The line PF 013562 showed the most outtanding result considering that its highest severity riched only 6,8% 15 days after inoculation. Other lines also showed progresso f the disease. The identification of wheat lines double-haploid of the cross BR 18 x Frontana with partial resistance to brown spot shows that is possible to select genotypes with such characteristic in breeding programs aiming at to develop comercial varieties resistante to this diseases. A transgressive segregation was also observed to AUDPC and to severity of brown spot, on this population studied. The herdability values were 9% to 85%. It was observed a normal distribution on most lines within the parents BR 18 and Frontana, indicating that the genetic inheritance that governs this population is determined by high number of genes that could be considered a polygenic resistance with additive effects